Student Experience with Local Culture Textbook in Learning Indonesian Language for Foreigner - Yunianti, Sofi; Fatin, Idhoofiyatul; Affandy, Ali Nuke; Istianingrum, Riska (Ideas Publishing, 2024)
Learning language is automatically learning the culture. However, there is limited book in learning Indonesia language which is discussed about culture. This article purpose is to find out what was the attitude of students towards the textbooks adopted. Hence, it is examined by using qualitative since this study analyzed the phenomena which occurred in Indonesian Language Learning for Foreigner class (BIPA). The Subject of the study is BIPA students which consists of 6 foreigner students. The data is taken from the questionnaire and analyzed based on the student’s opinion. The result presents the students opinion towards the textbooks is excellent.